KEPEMIMPINAN PROFESIONAL DALAM MEMBANGUN VISI DAN TUJUAN BERSAMA DI SMPN NEGERI 9 MUARO JAMBI - Rusmini Rusmini; Muhajirin; Ahmad Syukri; Asrulla (LPPM Universitas Cipta Mandiri, 2024)
The professional duty of the school principal is to build a shared vision and goals to achieve quality education. This is manifested by the principal of SMPN 9 Muaro Jambi. This qualitative research uses a qualitative descriptive approach. The subjects of this research are the school principal, vice principal, and teachers. Data collection is done through observation, interviews, and documentation techniques. Data analysis uses the Miles and Huberman model, including data reduction, data display, and data conclusion. The results of this research show that professional leadership of the principal of SMPN 9 Muaro Jambi is an ability possessed by a professional leader to mobilize organizational resources, especially human resources, to achieve expectations. This ability determines whether a leader is successful. The professional duty of the principal of SMPN 9 Muaro Jambi is to build a shared vision and goals, creating a sense of commitment within a group by creating a shared picture of the future, principles, and practical guidelines that are expected to achieve the future.